Cơ sở dữ liệu trắc lượng thư mục1 - Nguyễn, Huy Chương (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Bibliometrics is used to evaluate the work of a researcher as well as the capacity of a research institution and a research management organization. In order to conduct bibliometric analysis, it's necessary to have databases to provide information for monitoring and evaluation. The article analyzes the current status of bibliometric databases and recommends to design bibliometric database with SQL server in order to organize, store and analyze bibliometric-related information.